Lower dietary variety is a relevant factor for malnutrition in older Japanese home-care recipients: a cross-sectional study - Taeko Tsuji (BMC Geriatrics, 2019)
Abstract Background Nutritional status of the older people is affected by various life-style factors. Although dietary habit is one of the life-style factors, it is unknown which of older home-care recipients’ dietary habits are associated with malnutrition. The purpose of this study was to examine the association of dietary variety, as an evaluation index for dietary habits, with malnutrition in Japanese older home-care recipients. Methods This cross-sectional study was conducted in a single city, Hyogo Prefecture, Japan between July and October 2016. Three hundred thirty-three community-dwelling older care recipients (aged 65 years or older who were receiving home-visit nursing care services) were enrolled. Their nutritional status (Mini Nutritional Assessment®-short form: MNA®-SF), dietary variety (Food frequency score [FFS]), socio-demographic characteristics (age, sex, marital status, etc.), health indicators (comorbidity [Charlson Comorbidity Index] and dysphagia status [Dysphagia Severity Scale]) were assessed. The participants were classified into two groups: malnourished (0–7 points) and non-malnourished (8–14 points), according to their MNA®-SF scores. Multivariate logistic regression analysis was used to examine the factors associated with malnutrition. Results A total of 317 participants were analyzed (118 men, 199 women, median age: 84 years). Compared to the fourth (highest) quartile of FFS, odds ratios (OR) (95% confidence intervals [CI]) of the third, second, and first (lowest) quartiles of FFS were 1.08 (0.42–2.80), 1.29 (0.56–2.98), and 2.30 (1.02–5.19), respectively (p for trend = 0.049). Higher Charlson Comorbidity Index score and the presence of dysphagia were also significantly associated with malnutrition (OR: 2.08, 95% CI: 1.08–4.00 and OR: 3.86, 95% CI: 2.08–7.17, respectively). Conclusion Lower dietary variety was significantly associated with malnutrition in Japanese older home-care recipients.